2006
DOI: 10.1177/08830738060210050101
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Status in Pediatric Outpatients on Antiepileptic Drug Monotherapy

Abstract: Drug-induced osteopenia has been reported in institutionalized children on chronic antiepileptic drug therapy. The aim of this study was to assess longitudinally bone mineral status in pediatric outpatients on antiepileptic drug monotherapy. The study group consisted of 30 ambulatory children on a normal diet: 15 on valproic acid, 11 on carbamazepine, and 4 on phenobarbital monotherapy. Bone mineral density, serum active vitamin D (1,25-dihydroxyvitamin D), and certain biochemical markers of bone formation (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 21 publications
0
29
0
4
Order By: Relevance
“…Of the few longitudinal studies, some revealed bone loss in children and adults as well as changes in indices of bone and mineral metabolism. [2][3][4][5] None have evaluated the effects of individual AEDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the few longitudinal studies, some revealed bone loss in children and adults as well as changes in indices of bone and mineral metabolism. [2][3][4][5] None have evaluated the effects of individual AEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Of the few longitudinal studies, some revealed bone loss in children and adults as well as changes in indices of bone and mineral metabolism. [2][3][4][5] None have evaluated the effects of individual AEDs.We previously reported results of a cross-sectional study of bone mineral density (BMD) and indices of bone and mineral metabolism in premenopausal women with epilepsy taking Herein, we report our findings in women treated with one of four AEDs in monotherapy followed up for 1 year. Given the biochemical evidence of increased turnover at baseline in women receiving phenytoin, we hypothesized that there would be more bone loss in this group.…”
mentioning
confidence: 99%
“…Во многих работах показано, что терапия КБЗ вызы-вает снижение МПК в поясничном отделе позвоночника [29][30][31][32][33], шейке бедра [6,10,31,33], предплечье [33, 34] и пя-точной кости [35].…”
Section: традиционные пэпunclassified
“…[38] у пациентов, принимающих КБЗ, показано увеличение уровня щелочной фосфатазы с изменением других марке-ров костного образования и резорбции, однако концентра-ция витамина D оставалась в пределах нормальных значе-ний. В двух других параллельных исследованиях продемон-стрировано отсутствие корреляции между уровнем витами-на D в сыворотке крови и снижением МПК при приеме КБЗ [10,30]. В работе А. Verrotti и соавт.…”
Section: традиционные пэпunclassified
See 1 more Smart Citation